The Handbook of Mummy Studies 2020
DOI: 10.1007/978-981-15-1614-6_14-1
|View full text |Cite
|
Sign up to set email alerts
|

Archaeoparasitology of Korean Mummies

Abstract: Archaeoparasitology is now a rapidly progressing research field, providing comprehensive context about parasitism of the past and the origins and evolution of each parasite species. As in other continents, historical parasitic infection patterns in East Asia have been successfully reconstructed by archaeoparasitological research. By interdisciplinary collaboration with archaeologists, parasitologists in South Korea also have achieved meaningful academic progress in studies on various specimens uncovered at arc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
1
0
0
Order By: Relevance
“…This is much higher than the 4.6% infection rate of C.sinensis in the 1971 national survey [ 2 , 9 ]. As seen in our previous studies [ 2 , 10 ], we found that the overall rates of A. lumbricoides , T. trichiura , and C. sinensis decreased dramatically from Joseon to the modern period. We also note that Goryeong mummy is the 4th Joseon case to show Metagonimus spp.…”
Section: Discussionsupporting
confidence: 85%
“…This is much higher than the 4.6% infection rate of C.sinensis in the 1971 national survey [ 2 , 9 ]. As seen in our previous studies [ 2 , 10 ], we found that the overall rates of A. lumbricoides , T. trichiura , and C. sinensis decreased dramatically from Joseon to the modern period. We also note that Goryeong mummy is the 4th Joseon case to show Metagonimus spp.…”
Section: Discussionsupporting
confidence: 85%